A multidisciplinary team-based model of palliative treatment and nursing for a patient with end-stage cancer (多学科协作模式下1例肿瘤终末期患者的姑息治疗和护理) - CUI Lishuan (崔立爽); LI Linlin (李琳琳); SONG Dun (宋钝); ZHANG Jinhua (张金华) (中西医结合护理)
A multidisciplinary team (MDT) is a professional group of surgeons, oncologists and other medical and nursing experts who makes decisions about a specific subject in a collective manner, and best course of treatment and nursing plan will be implemented by the multidisciplinary team. This paper summarized the experience of adopting a MDT-based model of palliative treatment and nursing for a patient with end-stage cancer. Based on the nursing risk assessment, comprehensive interventions including wound management, nutrition support and psychological support were carried out to improve the quality of palliative care. (多学科协作(MDT)模式是由来自外科、肿瘤内科、放疗科、影像科、病理科等科室专家组成的工作组, 针对某一疾病, 通过定期会诊形式, 提出适合肿瘤终末期患者的最佳治疗方案, 继而由相关学科或多学科联合执行该治疗方案。 本文总结多学科协作模式下1例肿瘤终末期患者的姑息治疗和护理经验。在完善护理评估的基础上, 基于MDT模式加强患者伤口管理、营养干预、心理支持等, 提升缓和医疗服务质量。)